2002
DOI: 10.1007/s003830100608
|View full text |Cite
|
Sign up to set email alerts
|

Protrusion of a peritoneal catheter through the umblicus: an unusual complication of a ventriculoperitoneal shunt

Abstract: Protrusion of a ventriculoperitoneal (VP) shunt through the umblicus is one of the rare complications of shunt insertion reported in the medical literature. One such case is presented here in a child in whom a VP shunt had been placed for congenital hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The review of literature revealed several reports regarding extrusion or abnormal migration of distal end of shunt. [ 4 5 6 7 8 9 10 ] Although most common type of migration is within the peritoneum but extrusion through anus, vagina, urethra, umbilicus, into congenital inguinal hernial sac, through anterior abdominal, chest, or from cervical region have also been occasionally reported. [ 1 4 5 6 7 8 9 10 ] The other common extraperitoneal sites are migration into thorax through the diaphragm resulting in CSF hydrothorax.…”
Section: Discussionmentioning
confidence: 99%
“…The review of literature revealed several reports regarding extrusion or abnormal migration of distal end of shunt. [ 4 5 6 7 8 9 10 ] Although most common type of migration is within the peritoneum but extrusion through anus, vagina, urethra, umbilicus, into congenital inguinal hernial sac, through anterior abdominal, chest, or from cervical region have also been occasionally reported. [ 1 4 5 6 7 8 9 10 ] The other common extraperitoneal sites are migration into thorax through the diaphragm resulting in CSF hydrothorax.…”
Section: Discussionmentioning
confidence: 99%
“…In the paediatric literature Wani et al . presented a single case of an 18 month old with congenital hydrocephalus presenting with fever some 6 months post VP shunt insertion [3]. In this case due to the small size of the patient, the distal catheter could easily be palpated at the umbilicus making the diagnosis obvious and easily confirmed with bedside ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough search of the medical literature reveals a report of 12 such cases [1,5,6,7,8,9,10] of which catheter protrusion through the umbilicus was seen in 3 [1, 8, 9]. Congenital hydrocephalus remains a common cause for CSF diversion surgery, especially among pediatric patients [1, 5, 7, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hydrocephalus remains a common cause for CSF diversion surgery, especially among pediatric patients [1, 5, 7, 9]. Numerous reports have tried to explain the pathogenesis of such a complication, which includes anatomical weakness [1], umbilical abscess [8], persistent umbilical vein [6], perivisceritis [6] or persistent urachal remnant [10].…”
Section: Discussionmentioning
confidence: 99%